2016
DOI: 10.1007/s11042-016-3780-9
|View full text |Cite
|
Sign up to set email alerts
|

Fighting exclusion: a multimedia mobile app with zombies and maps as a medium for civic engagement and design

Abstract: This paper presents a study on urban data crowdsourcing driven by Geo-Zombie, a multimedia mobile application we designed and developed to engage pedestrians in taking note of urban architectural impediments and facilities by documenting them through pictures and multimedia data. Geo-Zombie aims at transforming the civic activity of contributing into a virtual gamified experience where players attempt to escape from horrific situations in which zombies are ready to cannibalize unsuspecting walkers. In some sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 39 publications
0
51
0
4
Order By: Relevance
“…Most of the studies in gamification embedded a combination of motivational factors: points, leaderboards, and levels [41], dual point systems and rating [6,37,38], leaderboards, ranking, unlocking information [47], progress, points, ranking, network [48], leaderboard, badges [49], challenge, progress bar, theme, rewards [44], badges, levels [50], points, levels, avatar [44]. The distinct effect of point scores on users' behavior and motivation is still vague, a gap we wish to narrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies in gamification embedded a combination of motivational factors: points, leaderboards, and levels [41], dual point systems and rating [6,37,38], leaderboards, ranking, unlocking information [47], progress, points, ranking, network [48], leaderboard, badges [49], challenge, progress bar, theme, rewards [44], badges, levels [50], points, levels, avatar [44]. The distinct effect of point scores on users' behavior and motivation is still vague, a gap we wish to narrow.…”
Section: Discussionmentioning
confidence: 99%
“…Further analyzing the scoring mechanism in regard to the four types of crowdsourcing systems based on [16] reveals that in most crowd-processing, crowd rating and crowd solving settings, the scoring mechanism design measures task fulfillment. Only few studies to date have provided an explanation or describe how the scoring mechanism is actually designed in crowdcreated settings [11,38,40,44]. Consequently it remains a question to explore.…”
Section: Motivational Factors Of Points and Scoresmentioning
confidence: 99%
“…In order to motivate them, they used a system of repayment, from points and ranking. Prandi et al [21] explored ways to encourage users to upload geo-tagged photos of obstacles on their system, which identifies viable paths for people with movement difficulties. They found that gamification features increased the involvement of contributors.…”
Section: Citizen Science and Gamificationmentioning
confidence: 99%
“…In contrast to Roccetti et al [20], we gave the users the ability to upload whatever route they want, even if they don't usually follow it, because in our research we aim to record all possible pedestrian routes. Although the gamification of the mobile application could be considered as lightweight in comparison to related work (e.g., [21]), it has been sufficient to collect enough data for preparing a pedestrian map of a small city with forty thousand inhabitants. Moreover, similar lightweight gamification methods have proven very successful in commercial services, such Foursquare, which motivates user to check-in just by offering (mayor) badges.…”
Section: Citizen-science and Gamificationmentioning
confidence: 99%
“…Other authors emphasise that citizens still engage but the ways of communication have changed drastically, complementing and partly even replacing community meetings and co-located participatory action with digital tools and social media (Ekman & AmnĂĄ, 2012;Gordon & Mihailidis, 2016;Hay, 2007;Kleinhans, van Ham, & Evans-Cowley, 2015;Macafee & De Simone, 2012;Marichal, 2013;Skocpol, 1997;Tufekci & Wilson, 2012). In different planning and design-related disciplines, digital tools for online participation, such as e-democracy portals, online consultations, e-voting, crowdsourcing, blogging, social network platforms, mobile apps, community GIS, and online deliberation, have gained increased attention as instruments to involve citizens and actor groups who either are too busy or not interested to participate in co-located meetings (e.g., Ahmed, Mehdi, Moreton, & Elmaghraby, 2015;Belluci et al, 2015;Kelley & Johnston, 2011;Prandi, Roccetti, Salomoni, Nisi, & Jardim Nunes, 2017).…”
Section: Introductionmentioning
confidence: 99%